On the Egyptian textual evidence of the myth of Thoth in Plato's Phaedrus - Carvalhar, Carlos (Revista Archai, 2025)
In Phaedrus, the myth of Thoth explicitly alludes to Egypt and it is possible to find parallels with texts written in Egyptian, showing that Plato had some knowledge of Egyptian philosophy. This article will highlight some of the parallels and comment on this bibliography, since they are articles and chapters written in different languages and that do not converse with each other. It will comment on the Book of Thoth and discuss the thematic similarities with the tale Setne I, in relation to the dual role of writing as φάρμακον. It will then examine the relationship between Egyptian texts and Phaedrus. In doing so, it will be possible not only to show the state of the art of this discussion, but also to explore in greater depth the issues surrounding these two divergent conceptions of the role of writing and the transmission of knowledge.